2010
DOI: 10.2139/ssrn.1732862
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Specific Performance Information can Worsen the Tragedy of the Commons: Experimental Evidence

Abstract: The main aim of this article is to investigate the behavioral consequences of the provision of subject-specific information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Firstly, there is limited anonymity: actors may know each other and therefore be able to identify the source of a given piece of information. The availability of personspecific information may exacerbate the effects of the tragedy of the commons (Villena and Zecchetto, 2010) or negatively impact conditional cooperation (Janssen 2013). Secondly, the disclosure of private information could encourage strategic behaviour, for instance by providing incorrect information so competitors do not benefit.…”
Section: Information Sharing For the Management Of Collective Naturalmentioning
confidence: 99%
“…Firstly, there is limited anonymity: actors may know each other and therefore be able to identify the source of a given piece of information. The availability of personspecific information may exacerbate the effects of the tragedy of the commons (Villena and Zecchetto, 2010) or negatively impact conditional cooperation (Janssen 2013). Secondly, the disclosure of private information could encourage strategic behaviour, for instance by providing incorrect information so competitors do not benefit.…”
Section: Information Sharing For the Management Of Collective Naturalmentioning
confidence: 99%
“…Research on global common goods has pointed out the fact that information can be considered to be a common good, emphasizing the difference between information, artifacts and facilities (Hess and Ostrom, ). Other research on information in the context of commons management has shown its importance, for instance through studies of the effects of information availability and granularity for conditional cooperation (Villena and Zecchetto, ; Janssen, ; Bell et al ., ). Information can be shared one‐to‐one (Bodin and Crona, ) or with groups of people during meetings or through information sharing artifacts (Allen and Kilvington, ; Pahl‐Wostl, ).…”
Section: Introductionmentioning
confidence: 99%